R REFLEKSI KRITIS ATAS EKSISTENSI AGAMA SEBAGAI PESAN TUHAN - Louk, Vabianus; Elbert Biliyandi, Mateus; Bhanu Viktorahadi, R.F. (Integritas Terbuka: Peace and Interfaith Studies, 2023)
This research aims to critically reflect on the existence of religion as God's message. Religion is considered to have the potential to change a person's behavior through moral values sourced from the Holy Book or Al Quran as a source of faith or revelation. The main purpose of religion is believed to be the guidance of rules that lead to a better direction, reflecting God's message. However, the existence of religion begins to be questioned when it is used for subjective interests, creating problems in society. The research method used in this paper is a literature review, by referring to various writings, journal articles, and books as supporting sources to strengthen the argument. This research aims to answer critical questions about whether religion can still be categorized as a message of God's revelation when it experiences misuse that creates conflict in society. The results of this critical reflection are expected to provide new insights related to the existence of religion as moral guidance and God's message, as well as how its misuse can reduce the essence and original purpose of religion.